2011
DOI: 10.2217/pgs.10.212
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABCB1 Gene Polymorphisms and Their Haplotypes with Response to Antiepileptic Drugs: a Systematic Review and Meta-Analysis

Abstract: Our data suggest that the haplotypes of these loci may not be involved in the response to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 67 publications
1
43
1
2
Order By: Relevance
“…In a Japanese cohort, even the opposite effect was observed [185]. In the meantime, several meta-analyses comprising 3371 [186], 6673 [187] and 7067 [188] patients have corroborated the missing significant effect between ABCB1 genetics and drug-resistant epilepsy.…”
Section: Antiepileptic Drugsmentioning
confidence: 88%
“…In a Japanese cohort, even the opposite effect was observed [185]. In the meantime, several meta-analyses comprising 3371 [186], 6673 [187] and 7067 [188] patients have corroborated the missing significant effect between ABCB1 genetics and drug-resistant epilepsy.…”
Section: Antiepileptic Drugsmentioning
confidence: 88%
“…However, a series of case-control studies about C3435T polymorphism and resistance to AEDs yielded inconsistent results (Seo et al, 2006;Kim et al, 2006;Shahwan et al, 2007;Hung et al, 2007;Kim et al, 2009;Kwan et al, 2009;Vahab et al, 2009;von Stülpnagel et al, 2009;Grover et al, 2010;Dong et al, 2011;Kumari et al, 2011;Meng et al, 2011;Sayyah et al, 2011;Seven et al, 2014). Further, six meta-analyses (Bournissen et al, 2009;Haerian et al, 2010Haerian et al, , 2011aLeschziner et al, 2007;Nurmohamed et al, 2010;Li et al, 2014) attempted to analyze the findings of these case-control studies, but consistent results were not obtained due to the presence of between-study heterogeneity. Meta-analyses are based on the assumption of etiologic homogeneity across studies, so they may not detect real effects in the presence of between-study heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies were unable to prove an association between G2677T/A polymorphism and resistance to AEDs (Kim et al, 2006;Shahwan et al, 2007;Vahab et al, 2009;von Stülpnagel et al, 2009;Grover et al, 2010;Dong et al, 2011;Meng et al, 2011;Sayyah et al, 2011;Haerian et al, 2011b;Seven et al, 2014), while others reported a significant association (Hung et al, 2007;Kwan et al, 2009;Subenthiran et al, 2013); moreover, a study from India indicated an association of allele A with drug-resistant epilepsy (Kumari et al, 2011). In addition, a recent meta-analysis involving G2677T/A polymorphism (Haerian et al, 2011a) did not find a significant association between G2677T/A polymorphism and resistance to AEDs in epilepsy (P = 0.07-0.96). However, it should be pointed out that this meta-analysis included two studies that deviated from HWE.…”
Section: Studymentioning
confidence: 91%
See 1 more Smart Citation
“…Stratification to ethnic groups revealed no further evidence (Bournissen et al, 2009). The most comprehensive meta-analysis was published very recently comprising 7067 patients (Haerian et al, 2011) (Table 12.3).…”
Section: Epilepsymentioning
confidence: 93%